Use of Wireless Technologies in the Automation of Technological Processes - Qizi, Yo'ldoshova Hilola Baxtiyor (Research Parks Publishing LLC, 2023)
Necessary conditions for the system of communication networks in the management of technological processes effectively support hybrid in process networks and traffic, durability, reliability, security and scalability technological management is important in the industrial environment. To develop an industrial-strength wireless network that can work hard process automation requirements, network restrictions is the design that includes the hardware and software components used. to the system to achieve the required quality of service, a broad view of systems should be considered as a general network-based indicator and applications based on operation, interaction and cooperation formed on the basis of individual components. To reach the accepted network, various problems are solved. As part of this study, three specific issues were addressed: the problem of time synchronization distributed systems, closed-loop management of limited resources wireless network and transmission power monitoring. wireless field nodes are created. They solve a limited problem. That's it maximum use of available resources in the nodes of the distributed area is envisaged. Recent developments in wireless communication technologies that create new opportunities for wireless communication gas and communication with field equipment in many fields examples include processes in oil distribution and chemical refining. Wireless communications can help the above areas improve the plant and knowledge, measurements by getting filler where wired communication is not allowed, operations and devices can be attached to the technological automation system. Operational field communication network requirements active support for hybrid traffic, durability, reliability, in an industrial environment, it is necessary to take advantage of security and scalability. In addition, the organization of such a network at scale the fact that it does not have any strong network is a concern in this regard and creates several problems.